Clostridium sordellii Phospholipase C: Gene Cloning and Comparison of Enzymatic and Biological Activities with Those of Clostridium perfringens and Clostridium bifermentans Phospholipase C - Karasawa, Tadahiro (American Society for Microbiology, 2003)
The gene encoding Clostridium sordellii phospholipase C (Csp) was cloned and expressed as a histidine-tagged (His-tag) protein, and the protein was purified to compare its enzymatic and biological activities with those of Clostridium perfringens phospholipase C (Cpa) and Clostridium bifermentans phospholipase C (Cbp). Csp was found to consist of 371 amino acid residues in the mature form and to be more homologous to Cbp than to Cpa. The egg yolk phospholipid hydrolysis activity of the His-tag Csp was about one-third of that of His-tag Cpa, but the hemolytic activity was less than 1% of that of His-tag Cpa. His-tag Csp was nontoxic to mice. Immunization of mice with His-tag Cbp or His-tag Csp did not provide effective protection against the lethal activity of His-tag Cpa. These results indicate that Csp possesses similar molecular properties to Cbp and suggest that comparative analysis of toxic and nontoxic clostridial phospholipases is helpful for characterization of the toxic properties of clostridial phospholipases.